The Paradox of Corporate Social Responsibility Reporting: A Literature Review on the Gap Between CSR Commitments and Corporate Misbehavior: CSR reporting, corporate misbehavior, greenwashing, stakeholder engagement, reporting standards. - Hanifah; Irawan, Dadang (Journal of Economic and Leadership, 2024)
This qualitative literature review explores the paradox of Corporate Social Responsibility (CSR) reporting, highlighting the gap between corporate commitments and actual behavior. The review synthesizes recent research, revealing that CSR disclosures often serve as tools for legitimacy rather than genuine accountability. Issues such as greenwashing and inconsistent reporting standards undermine the credibility of CSR reports, limiting their impact on corporate behavior. The review emphasizes the importance of stakeholder pressure in enhancing accountability and calls for standardized reporting frameworks to improve transparency. Despite the widespread adoption of CSR reporting, significant challenges remain in aligning disclosures with authentic corporate practices. This study underscores the need for concerted efforts from companies and regulators to ensure that CSR reporting promotes ethical business conduct.